A relaçao entre gestao da informaçao e gestao documental na arquivologia: mapeamento do tema em publicaçoes científicas brasileiras - Pazin Vitoriano, Marcia Cristina de Carvalho (2017)
It presents a study about the presence of the Information Management theme in archival-themed articles. The objective is to identify how the scientific community has dealt with the existence of an interface between the two areas regarding the presence of elements of Information Management, advocated by Information Science, in relation to the specific activities of Document Management. As a methodological procedure, it was a survey of bibliography produced over the last two decades (1997-2017) by Brazilian researchers on the subject of Document Management, aiming to identify, among the works listed, those that deal with the subject of Information Management, central or subsidiary and how these issues are addressed. As a result, 21 articles were identified, divided into three categories of analysis, which demonstrate the state of discussions about the relationship between Information Management and Document Management